(untitled) (Bioagro, 2023)
By using hydroponics makes possible to increase the use of nutrients by crops; however, the balance of the nutrient solution (NS) must be adequate, otherwise the plant response may be negatively affected. The objective of this research was to determine during three stages the growth of lettuce plants under hydroponics, using macronutrients (NO3-, H2PO4-, SO42- and K+, Ca2+, Mg2+) in the following five respective proportions: 60:5:35 and 35:45:20 (NS-1-control), 80:2.5:17.5 and 35:45:20 (NS-2), 40:7.5:52.5 and 35:45:20 (NS-3), 60:5:35 and 43.7: 38.9:17.3 (NS-4) and 60:5:35 and 20:55.4:24.6 (NS-5). The trial was conducted in a randomized block design with six replicates. The chlorophyll index (CI), foliar area (FA) and plant fresh weight (PF), as well as dry weight of leaves (LDW), bud (BDW) and root (RDW) were determined. The NS-2 showed to be superior than other proposed treatments in the three stages in the variables of FP, FA and IC, and in certain stages it was superior to the control treatment. In the dry weight variables, there were only differences in the final stage for LDW and RDW in which NS-2 outperformed other proposed NS, although did not differ from Steiner’s NS (control). The treatment with a high proportion of nitrate (NS-2) outperformed the rest of the treatments in different variables, as well as eventually Steiner’s NS, so it should be considered in future evaluations of nutrient solutions for leafy crops.